Identity, Dignity and the Politics of Resentment: Limits of Globalization - Callaway, H. G. (Ruch Filozoficzny, 2023)
This paper focuses on moral, legal and constitutional issues arising from debates and political conflicts centered on identity, human dignity, recognition and identity politics.[1] In his 2018 book, Identity, the Demand for Dignity and the Politics of Resentment, Stanford University political scientist Francis Fukuyama addresses themes properly considered matters of political philosophy and the philosophy of law: How are we to navigate between traditional, sometimes ethnic-racial or religious, and unitary conceptions of the nation-state on the one hand, and the threat of identitarian fragmentation on the other? Fukuyama affirms the importance of the concepts of human dignity and identity, and he also criticizes contemporary identity politics—which he views as a danger to liberal democracy. “The rise of identity politics in modern liberal democracies,” writes Fukuyama, “is one of the chief threats that they face;” and “unless we can work our way back to more universal understandings of human dignity, we will doom ourselves to continuing conflict.” Fukuyama’s criticism of identity politics has more recently found some parallels in writings of the prominent American journalist George Packer and his 2021 book, Last Best Hope. Drawing on Fukuyama’s arguments and Packer’s complementary criticism from the center-left, this paper also raises a related question of whether the well-reasoned case against identity politics as a threat to liberal democracy, national unity, and purpose does not create greater room for a skepticism of fast-paced and ambitious (“Wilsonian”), liberal-internationalist goals and globalization. Greater emphasis on political consensus at home may strengthen the hand of American foreign policy in support of liberal democracy, partly because we now look back with well-founded skepticism on neo-conservative interventionism and “forever wars.” The argument is that just and needed limits on globalizing internationalism are implicit in the criticism of identity politics. Having lost the unity of purpose of Cold-War liberalism, we have yet to find a “golden mean” avoiding divisive ethnic nationalism and identitarian fragmentation.